Elements of Multimedia, 1st edition - Banerjee, Sreeparna (Chapman and Hall/CRC, 2020)
Elements of Multimedia presents a systematic introduction and integrated overview of the state-of-the-art innovations that make Multimedia a rapidly evolving technology in the digital domain. This book is also an invaluable resource for applied researchers. Some of the salient features of the book include: